Quantifying antibiotic use in typhoid fever in India: a cross-sectional analysis of private sector medical audit data, 2013–2015. Issue 10 (17th October 2022) - Fazaludeen Koya, Shaffi; Hasan Farooqui, Habib; Mehta, Aashna; Selvaraj, Sakthivel; Galea, Sandro
Abstract : Objectives: To estimate the antibiotic prescription rates for typhoid in India. Design: Cross-sectional study. Setting: Private sector primary care clinicians in India. Participants: The data came from prescriptions of a panel of 4600 private sector primary care clinicians selected through a multistage stratified random sampling accounting for the region, specialty type and patient turnover. The data had 671 million prescriptions for antibiotics extracted from the IQVIA database for the years 2013, 2014 and 2015. Primary and secondary outcome measures: Mean annual antibiotic prescription rates; sex-specific and age-specific prescription rates; distribution of antibiotic class. Results: There were 8.98 million antibiotic prescriptions per year for typhoid, accounting for 714 prescriptions per 100 000 population. Children 10–19 years of age represented 18.6% of the total burden in the country in absolute numbers, 20–29 year age group had the highest age-specific rate, and males had a higher average rate (844/100 000) compared with females (627/100 000). Ten different antibiotics accounted for 72.4% of all prescriptions. Cefixime–ofloxacin combination was the preferred drug of choice for typhoid across all regions except the south. Combination antibiotics are the preferred choice of prescribers for adult patients, while cephalosporins are the preferred choice for children and young age. Quinolones were prescribed as monotherapy in 23.0% of cases. Conclusions: Nationally representative private sector antibiotic prescription data during 2013–2015 indicate a higher disease burden of typhoid in India than previously estimated. The total prescription rate shows a declining trend. Young adult patients account for close to one-third of the cases and children less than 10 years account for more than a million cases annually.